Formative Research in Higher Education: Some Reflections. (20th February 2015) - Valencia, Jackeline; Macias, Jackeline; Valencia, Alejandro
Abstract: Research is considered fundamental in the formation process of students in higher education institutions (HEI). It has been positioning pedagogic strategies to promote its development such as formative research. It represents an effective alternative that allows the stimulation of students' skills improving the quality and structure of the research and professional profile of the student training. In this paper is presented the role and importance of formative research in professional training qualification. It considers how it is understood the concept of formative research, mentioning some techniques or strategies that have enabled in its development as a pedagogic activity in School or HEI.